Pobreza e raça: intersecções em um terreiro de umbanda em Acarape-CE - Lima, Antônio Ailton de Sousa (2020)
This paper discusses the historical and conceptual engenderings of the categories of poverty and race, as well as their intersections in terms of their intersections. Based on the assumption that, both socially and academically, both categories are understood in independent ways, in which one is seen as an under-representation of the other, it evokes discussions that reflect on the contrary. It is through a decolonial and intersectional perspective that we build subsidies to establish the relationship pointed out here in Umbanda temple contexts. Thus, the general objective is to analyze the intersections between the markers of poverty, race and religion as resistance strategies experienced by Umbanda practitioners in Acarape-CE. As specific objectives, it seeks to: (I) conduct a systematic review from the descriptors of race and poverty; (II) investigate the life trajectories of each practitioner considering the relationship between race and religion; (III) understand how Umbanda practitioners associate their religious practice with poverty; and, (IV) describe the resistance strategies of Umbanda practitioners facing the intersection of poverty and race. Thus, the problematic around the psychosocial processes of poverty and race crossed by the marker of religion is presented. The methodological proposal is based on a qualitative approach with a comprehensive bias, materializing through field visits, characterized by the technique of participant observation and semi-structured interview, considering as a criterion for participation to be an adult, practitioner of religion, resident of the city of Acarape and agree to participate in the research and sign the TECLE. Thus, all the content produced was analyzed based on Critical Discourse Analysis. We found distinct forms of racial (self)recognition and their relations with their religious institution. In addition, perceptions about poverty permeated by religious perspectives were observed, thus evidencing individual and collective practices as a way of confronting the devices of oppression inscribed in the daily lives of umbandistas in the city of Acarape-CE.